A diplomática contemporânea: na análise das correspondências do fundo “Interventor Magalhães Barata” - SOUSA, Luciene de Nazaré Furtado de (2021)
The objective of the research was to analyze the fund "Interventor Magalhães Barata" following the means of identification based on contemporary diplomatic and how this process contributes to the effectiveness of public and academic research. For this reason we have explained the concepts of identification extolling the importance of this process in the organization of the document mass already cited. We also show the trajectory and conceptual and practical development of the contemporary diplomatic applied especially in the correspondences of the fund "Interventor Magalhães Barata". Military by training, Joaquim de Magalhães Cardoso Barata, named the state of Pará in the decade of 1930 by Getúlio Vargas. Considered the "father of the poor" by the less affluent classes in Pará, he instituted a communication channel through correspondences that were destined to hear the people's complaints and petitions. He captivated friends and political enemies. This textual production, the letters, will be our basis for the identification of the information and characterization of the research. To extract the information from the documents we apply the standard of diplomatic analysis proposed by the author Tognoli (2013) being indispensable in this process of identification of correspondences.